A systems toxicology approach on the mechanism of uptake and toxicity of MWCNT in Caenorhabditis elegans. (5th September 2015) - Eom, Hyun-Jeong; Roca, Carlos P.; Roh, Ji-Yeon; Chatterjee, Nivedita; Jeong, Jae-Seong; Shim, Ilseob; Kim, Hyun-Mi; Kim, Phil-Je; Choi, Kyunghee; Giralt, Francesc; Choi, Jinhee
Highlights: Phagocytosis is a potential mechanism of uptake of MWCNTs. ER and oxidative stress are potential mechanisms of toxicity of MWCNTs. The transcriptomics, proteomics and functional genetic analyses provide insights into the toxicity of MWCNTs. The integrated systems toxicology approach will be useful for the development of an AOP. Abstract: The increased volumes of carbon nanotubes (CNTs) being utilized in industrial and biomedical processes carries with it an increased risk of unintentional release into the environment, requiring a thorough hazard and risk assessment. In this study, the toxicity of pristine and hydroxylated (OH–) multiwall CNTs (MWCNTs) was investigated in the nematode Caenorhabditis elegans using an integrated systems toxicology approach. To gain an insight into the toxic mechanism of MWCNTs, microarray and proteomics were conducted for C. elegans followed by pathway analyses. The results of pathway analyses suggested endocytosis, phagocytosis, oxidative stress and endoplasmic reticulum (ER) stress, as potential mechanisms of uptake and toxicity, which were subsequently investigated using loss-of-function mutants of genes of those pathways. The expression of phagocytosis related genes (i.e. ced-10 and rab-7 ) were significantly increased upon exposure to OH-MWCNT, concomitantly with the rescued toxicity by loss-of-function mutants of those genes, such as ced-10(n3246) and rab-7(ok511) . An increased sensitivity of the hsp-4(gk514) mutant by OH-MWCNT, along with a decreased expression of hsp-4 at both gene and protein level suggests that MWCNTs may affect ER stress response in C. elegans . Collectively, the results implied phagocytosis to be a potential mechanism of uptake of MWCNTs, and ER and oxidative stress as potential mechanisms of toxicity. The integrated systems toxicology approach applied in this study provided a comprehensive insight into the toxic mechanism of MWCNTs in C. elegans, which may eventually be used to develop an "Adverse Outcome Pathway (AOP)", a recently introduced concept as a conceptual framework to link molecular level responses to higher level effects.